Pelapisan Hydroxyapatite Pada Logam Titanium Material Sistem Gas Buang Mesin Diesel Generator - Lilik Budiyanto (Politeknik Ilmu Pelayaran Semarang, 2020)
Exhaust gas systems in diesel generators require heat-resistant materials. The use of titanium metal is designed for exhaust gas system materials. Material coating system for high temperature applications known as Thermal Barrier Coating (TBC) has been applied to diesel engine materials. TB has the ability to reduce temperature on the surface and protect thermal oxidation at high temperatures. This research discusses the coating of hydroxyapatite (HA) ceramic material on titanium metal which will be used as a flue gas system material with variations in coating temperature. The method used is testing the chemical composition of titanium metal, macro microscope testing of ceramic coatings and adhesion testing with variable temperature specimens 7000C, 8000C and 9000C.